PENGARUH KUALITAS PELAYANAN TERHADAP PENCAPAIAN TARGET PAJAK BUMI DAN BANGUNAN PADA BADAN PENDAPATAN DAERAH UPT TENGAH KOTA BANDUNG - Aditya Sidiq Nursyani; Hafied Noor Bagja (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
Land and building taxes have an important role and great benefits for people's lives. Land tax is the imposition of taxes on the surface of the earth (land) based on Law number 12 of 1985. While the building tax is the imposition of taxes on technical constructions that are permanently planted or placed on construction land, the technique can be used as a residence, or a place of business, or workable place. This study aims to determine the effect of service quality on the achievement of land and building tax targets. The sampling technique used is simple random sampling with 40 taxpayer respondents of Central UPT Bandung City. This research data uses primary data directly through questionnaires and analyzed using Statistical Product Service Solution. The data analysis method used in this research is to use a simple linear regression analysis method. In obtaining the necessary data, the preparation of this final project uses a research technique developed into closed questions with a Likert scale. The results of this study indicate that the effect of service quality (X1) has a positive and significant effect on the achievement of the land and building tax target (Y).